(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The development process in India has overlooked the marginalised and far-flung communities of the country. Access to good all-weather roads is recognised as an essential feature of any inclusive development strategy. Though governments at state and central level recognise the need to include these communities and habitats within the aegis of encompassing growth process, the state governments have been stuck with paucity of funds to undertake such developmental initiatives. The Pradhan Mantri Gram Sadak Yojana (PMGSY) was launched with the aim of providing good all-weather roads to the areas lacking such roads. The following article discusses the role of the Pradhan Mantri Grameen Sadak Yojna as a conveyor of growth and development. Secondary sources of data such as government reports and published material have been used in this article.